Comparing the Effectiveness of Lumbar Traction and Mckenzie Exercises versus Mckenzie Exercises Alone on Pain, Range of Movement and Function on Individuals with Intervertebral Disc Prolapse - AL murdef , Hussain Saleh Saud; Al Jafer , Fahad Mana Hussain; Al Jafer , Hussain Mana Hussain; Alkhamsan, Saleh Nasser Muhammad; alyami, Mohammed salem hadi; Al Sawydan, Mohammed Masfer M; Alsagrei, Habadan Saleh Mohammed; Alrabaie, Manea Ali; Abassil, Ali Mesfer Ali; Althobaiti, Amjad maqbul nawar (Journal of Ecohumanism, 2024)
Background: Low back pain has a huge economic impact on any healthcare system. Prolapse in lumbar intervertebral disc (PIVD) can lead to the development of LBP. Until the moment, there is inconclusive evidence regarding the best treatment option for PIVD. Aim: The purpose of this research was to examine the effectiveness of lumbar traction and McKenzie exercises versus McKenzie exercises alone on pain, range of movement and function on individuals with PIVD. Methods: A randomised clinical trail study design was utilised in this research. Participants were divided into two groups. Group A received lumbar traction and McKenzie exercises and Group B received McKenzie exercises alone. Different outcome measures such as goniometer readings, Oswestry Disability Index and numeric pain rating scale were used. Quantitative data was represented using descriptive statistics, while qualitative data was depicted through frequencies and percentage. Various statistical analyses were conducted to interpret the collected data. Results: Thirty-two individuals took part in this study. Sixteen individuals were allocated in each group in this study. There was no statistical significant difference between both groups in terms of gaining more range of movement and restoring lost function (p>0.05). However, there was a significant statistical change between groups in favour of Group A in terms of pain reduction (p<0.05). Conclusion: The findings of this study suggest that it will be more beneficial to add lumbar traction to McKenzie exercises to achieve more pain reduction. It seems that adding lumbar traction helped to relieve pain as it might helped in relieving excessive pressure exerted between lumbar vertebrates.